2021
DOI: 10.1186/s12876-021-01748-y
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between body composition and the histology of non‐alcoholic fatty liver disease: a cross‐sectional study

Abstract: Background Causes of non-alcoholic fatty liver disease and its progression include visceral fat accumulation and loss of muscle mass; however, which of the two phenomena is more critical is unclear. Therefore, we intended to examine the relationship between body composition and non-alcoholic fatty liver disease progression as indicated by fibrosis and the non-alcoholic fatty liver disease activity score. Methods This cross-sectional study comprised… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…In a prospective biopsy-confirmed NAFLD cohort of 521 patients indicated that low SMM was an independent predictor of significant fibrosis, ( 32 ) consistent with another biopsy-proven NAFLD cohort study ( 13 ). Miyake et al found that appendicular skeletal muscle mass remained associated with liver fibrosis estimated by liver biopsy after adjustment for confounding factors ( 33 ). In the present study, liver fibrosis was defined by transient elastography and similar results were obtain form our study.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective biopsy-confirmed NAFLD cohort of 521 patients indicated that low SMM was an independent predictor of significant fibrosis, ( 32 ) consistent with another biopsy-proven NAFLD cohort study ( 13 ). Miyake et al found that appendicular skeletal muscle mass remained associated with liver fibrosis estimated by liver biopsy after adjustment for confounding factors ( 33 ). In the present study, liver fibrosis was defined by transient elastography and similar results were obtain form our study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed an association between body composition and the risk for NAFLD [ 7 , 20 ]. A recent cross-sectional study has shown that fat mass indices were more strongly associated with fibrosis than were muscle mass indices [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed an association between body composition and the risk for NAFLD [ 7 , 20 ]. A recent cross-sectional study has shown that fat mass indices were more strongly associated with fibrosis than were muscle mass indices [ 7 ]. Other cross-sectional analyses in the Rotterdam Study reported that both high fat mass and lower lean mass were associated with NAFLD risk.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations